UV and Temperature-Sensing Based on NaGdF4:Yb3+:Er3+@SiO2-Eu(tta)3 - Nigoghossian, Karina [UNESP]; Messaddeq, Younès [UNESP]; Boudreau, Denis; Ribeiro, Sidney J. L. [UNESP] (American Chemical Society (ACS), 2017)
A multifunctional nanosystem was synthesized to be used as a dual sensor of UV light and temperature. NaGdF4:Yb3+:Er3+ upconverting nanoparticles (UCNPs) were synthesized and coated with a silica shell to which a europium(III) complex was incorporated. The synthesis of NaGdF4 UCNPs was performed via thermal decomposition of lanthanide ion fluoride precursors in the presence of oleic acid. To achieve sufficient water dispersibility, the surface of the hydrophobic oleate-capped UCNPs in the hexagonal phase was modified by a silica coating through a modified Stöber process through a reverse microemulsion method. An Eu(tta)3 (tta: thenoyltrifluoroacetonate) complex was prepared in situ at the silica shell. A dual-mode nanothermometer was obtained from a near infrared to visible upconversion fluorescence signal of Er3+ ions together with UV-excited downshifting emission from the Eu3+ complex. Measurements were recorded near the physiological temperature range (293-323 K), revealing excellent linearity (R2 > 0.99) and relatively high thermal sensitivities (≥1.5%·K-1). The Eu(tta)3 complex present in the silica shell was tested as the UV sensor because of the Eu3+ luminescence dependence on UV-light exposure time.